Implications in dental treatment during the use of antiresorptive drugs - a literature review - Dziewulska, Aleksandra; Kiełt, Weronika; Kozłowska, Julia; Broniec, Gabriela; Wajdowicz, Barbara; Kudła, Aleksandra; Czapiewska, Rozalia; Wróbel, Aleksandra; Pacek, Laura; Kowalska, Klaudia (Journal of Education, Health and Sport, 2024)
Introduction: Antiresorptive drugs such as bisphosphonates and denosumab are crucial for treating osteoporosis, metastatic bone disease, and hypercalcemia by inhibiting osteoclast function. They can lead to medication-related osteonecrosis of the jaw (MRONJ) following invasive dental procedures, requiring careful management to mitigate potential adverse effects. Purpose of work: Synthesis of knowledge about the impact of taking antiresorptive drugs on aspects of dental treatment. Materials and methods: Materials used in this study were found in the PubMed and Google Scholar database, using the following key words “antiresorptives”, “bisphosphonates”, “dental treatment”, “osteonecrosis of the jaw” Summary: Antiresorptive drugs like bisphosphonates and denosumab are essential for managing osteoporosis and other bone diseases but pose challenges in dental care, notably with risks such as medication-related osteonecrosis of the jaw (MRONJ). These medications influence treatment strategies across orthodontics, implantology, periodontal therapy, and endodontics, necessitating careful management to balance therapeutic benefits with potential dental complications.